Arterial Responses in Periparturient Beef Cows Following a 9-Week Exposure to Ergot (Claviceps purpurea) in Feed - Cowan, Vanessa; Grusie, Taylor; McKinnon, John; Blakley, Barry; Singh, Jaswant (Frontiers in Veterinary Science, 2019)
Ergot alkaloids are vasoconstrictors frequently detected in low concentrations in livestock feed. The Canadian Food Inspection Agency permits up to 3000 µg ergot alkaloids per kg cattle feed. The objective of this study was to examine the effects of feeding low concentrations of ergot alkaloids over nine-weeks on vascular dynamics in the caudal and internal iliac arteries of beef cows. A relationship between ergot alkaloid concentration in feed and hemodynamic changes in the caudal and internal iliac arteries was hypothesized. Periparturient beef cows were randomized into four groups and group fed mixed rations containing <15 g ergot alkaloids per kg of dry matter intake (Control, n=9), 48 g/kg (Low, n=9), 201 g/kg (Medium, n=8), 822 µg/kg (High, n=6). Three experimental periods comprised the study: pre-treatment (2 weeks), treatment (9 weeks), and post-treatment (3 weeks). B-mode and Doppler ultrasonography was performed weekly to measure hemodynamic endpoints. Plasma prolactin concentrations and rectal temperatures were measured weekly. Caudal artery diameter decreased (Treatment*Experimental Period i.e. Tx*EP p<0.001) by 14% in the High group during the treatment period. Reductions (Tx*EP p<0.001) in caudal artery blood flow (37%, 29%) and blood volume per pulse (29%, 11%) were recorded during the treatment period in the High and Medium groups. Internal iliac artery diameter and blood flow decreased (Tx*EP p≤0.004) by 13% and 40% during the treatment period in the Medium group. Moderate reductions (Tx*EP p≤0.042; 12-25%) in the mean blood velocity during the treatment and post-treatment periods and decreases (Tx*EP p≤0.01; 12-17%) in the peak systolic velocity of both arteries during the post-treatment period were also detected. Prolactin did not change during the treatment period (p=0.462). Rectal temperatures were within the normal physiological range for cattle. In conclusion, we documented moderate vasoconstriction in the caudal artery and the internal iliac artery in cows fed 201-822 g ergot alkaloids per kg DMI for nine-week period near parturition. The pattern of alterations was similar between the caudal and internal iliac arteries. Results of this study suggest that feeding up to 822 g/kg produce reversible pharmacological changes in beef cow vasculature and warrant reconsideration of current regulations for cattle.